Human and nonhuman rights approaches to environmental protection - West, Thomas Ernest Riversdale Barker (2017)
This thesis is concerned with the legal theory behind environmental rights. There are a number of different approaches that deploy rights as a mechanism to bring about environmental protection within international law, all of which can be termed ‘environmental rights’. These include a human right to a healthy environment and procedural environmental rights. But there are also theories that support a more innovative or extensive use of legal rights for protecting the natural world. Notably, many of these theories concern the introduction of nonhuman rights (animal rights or rights of nature). This thesis investigates the theory behind and the practical structure of these various approaches, as well as analysing the very concept of ‘rights’. The original contribution to knowledge is threefold. I present a case for a human right to a healthy environment to be defined broadly: measured according to human and ecosystem health, and conceived as a right of both individuals and peoples; I rigorously apply both Interest Theory and Hohfeld’s analysis of rights to human rights and thus construct a clear model for the structure of the sort of rights found in human rights (termed ‘vital rights’); and I extend the philosophical theory behind human rights (and in particular the concept of dignity) towards the growing field of rights of nature. Considered holistically, the thesis presents and suggests modes of thinking that seek to soften the divide between humanity and nature. This is done through a consideration of lived experience as always already ecologically embedded. As a result, the subject of vital rights (human rights included) should be understood as ecologically embedded living beings, opening the door to both nonhuman rights and new fields for human rights.